2022
DOI: 10.3390/atmos13040600
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall Simulations with Changing Resolution of Orography Based on the Yin-He Global Spectrum Model: A Case Study of the Zhengzhou 20·7 Extreme Rainfall Event

Abstract: In recent years, the study of numerical weather prediction (NWP) in complex orographic areas has attracted a great deal of attention. Complex orography plays an important role in the occurrence and development of extreme rainfall events. In this study, the Yin–He Global Spectrum Model (YHGSM) was used, and the wave number truncation method was employed to decompose the orographic data to different resolutions. The obtained orographic data with different resolutions were used to simulate the extreme rainfall in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Exp0 was the control experiment, in which the model's original orography was used. Wang et al [36] used the same configuration as exp0 when studying the effect of orographic resolution on NWP model simulations. They found that the YHGSM performed best using the orography of exp0.…”
Section: Processing Steps For Orographic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Exp0 was the control experiment, in which the model's original orography was used. Wang et al [36] used the same configuration as exp0 when studying the effect of orographic resolution on NWP model simulations. They found that the YHGSM performed best using the orography of exp0.…”
Section: Processing Steps For Orographic Datamentioning
confidence: 99%
“…There are 145 meteorological observation stations in the main precipitation area. Among them, Zhengzhou Station had an hourly rainfall of 201.9 mm at around 9:00 on 20 July 2021, setting a record in China and causing great damage to the environment and people [36]. Figure 5 shows hourly changes in total rainfall in the main precipitation area.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…Both strong ascending motion and abundant moisture supply were responsible for the occurrence of extreme flooding (Fu et al., 2022; S. Zhang et al., 2022). The regional numerical model, to some extent, can reproduce synoptic systems and extreme rainfall (X. Y. Wang et al., 2022; Yin et al., 2022). However, nearly all the operational models underpredicted the rainfall intensity (Shi et al., 2021; Q. J. Huang et al., 2022; X. J. Wang et al., 2022; H. X. Xu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%